The Status Of Marine Minerals Research Worldwide - Michael J. Cruickshank (International Marine Minerals Society, 1996)
Marine minerals are more than an academic curiosity as they represent the most significant global source of mineral materials for economically and ecologically sustainable development for the future. Minerals research is traditionally carried out by industry and thus, in the United States at least, applied research in marine minerals may not get the share of government funding or attention that more exotic programs for space exploration or future global disasters engender. Two recent events have significantly changed the status of marine minerals. Discoveries made in the last thirty five years indicate that the potential for mineral occurrences in the oceans and seabeds, area for area, is as high as for terrestrial lands. On this basis the global mineral resource base has been recently increased by a factor of four of which three quarters is underwater. The recently enacted Law of the Sea has mandated what is probably the most far reaching re-distribution of natural resources in human history, and has resulted in a peaceful subdivision of seabed jurisdictions between the coastal nations of the world which should significantly affect future mineral markets and the balance of economic powers. Significant applied research efforts are ongoing for marine minerals as an adjunct to commercial production in southern Africa for diamonds; and in many other parts of the world for sands for beach and coastal protection. Forward planing, including research and development activities focussed on future commercial production of metalliferous oxides, continues in Korea, China, Japan, India, and with lesser activity, in the United States, United Kingdom, Germany and the CIS. Annual expenditures for this work amount to millions of dollars. In all cases the environmental aspects of commercial produc¬tion are a significant part of the research. Geologic studies on the occurence and distribution of metal sulfides at plate boundaries continue on a regional basis in the Pacific.